The Effect of Tax Avoidance and Profitability on Earnings Management with Corporate Governance as a Moderating Variable (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2020) - Yustina, Nirma; Paryda, Paryda; Murtanto, Murtanto; Faisal, Aris Riantori (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to examine the impact of tax avoidance and moderated profitability on corporate governance and earnings management empirically. From 2016 to 2020, the population for this study was Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX). The sample for this study was constructed using a purposive sampling method, resulting in a sample of 46 manufacturing firms. Secondary data is what is being used. Techniques for documenting data collection from www.idx.co.id. MRA (Moderated Regression Analysis) was used to conduct the analysis, which was carried out using the Eviews version 10 application. The findings of this study indicate that tax avoidance has no discernible effect on earnings management, profitability has a significant negative effect on earnings management, corporate governance can mitigate the effect of tax avoidance on earnings management, and corporate governance can amplify the effect of profitability on earnings management.